PURA AGUNG SRIWIJAYA PALEMBANG - Fitriyana, Nur (JIA (Jurnal Ilmu Agama), 2015)
Hindu in South Sumatera initially developed in Pali area, because of the historical heritage the form of Bumi Ayu temple in Bumi Ayu village, Tanah Abang, Muaraenim Regency, South Sumatera Province. The style of art, statues of the Hindu pantheon that ever found in South Sumatra are estimated to come from around the VII - XV century AD. Thus, it can be presumed that Hinduism has evolved since before Sriwijaya spread its wings in the late seventh century. This teaching also develops in the years since then even in the X-XII AD century, Hinduism reached the peak of its development. This was proved by the discovery of statues and buildings on the site of the temple Tanah Abang. In the next period of Hinduism flourished around the XV century AD marked with the findings of three bronze statues in the city of Palembang. Then Hindus in southern Sumatra in the era of the 2000s did a wide range of religious activities. Then they established Pura Agung Sriwijaya .